HUBUNGAN STATUS EKONOMI, BUDAYA, DAN PENGETAHUAN DENGAN KEJADIAN PERNIKAHAN DINI PADA REMAJA DI DESA SUKARESMI TAHUN 2025 - Maelani, Risa; Barbara, Maria Awaldina Dua (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Early marriage is a social problem in Indonesia. In Sukaresmi Village, West Bandung Regency, this phenomenon is often experienced by adolescent girls aged 15–18 years. Data from the Sukaresmi Village Office shows that in 2025, there were 361 cases of early marriage from 1,156 adolescent girls. Factors that cause the high rate of early marriage include low levels of adolescent knowledge about early marriage, family economic conditions, and community culture that supports early marriage. This study aims to determine the relationship between economic status, culture and knowledge with the incidence of early marriage among adolescents in Sukaresmi Village in 2025. This study used a quantitative approach with a cross-sectional design. The sample consisted of 71 adolescent girls aged 15–18 years who were selected using a purposive sampling technique. Data collection was carried out through a questionnaire that had been tested for validity and reliability. Data analysis used the Chi-Square test with a significance level <0.05. The results of the study using the Chi-Square Test showed significant correlations for economic status (p=0.002), culture (p=0.000), and knowledge (p=0.000) between economic status, culture, and knowledge and the incidence of early marriage among adolescents.